Процес формування великомасштабних геоструктур в зоні колізії континентів - Лубков, М.В. (Геоінформатика, 2015)
На основі варіаційної скінченно-елементної методики для в’язкопружних багатошарових ортотропних оболонок змодельовано процеси утворення геоструктур у зоні колізії континентів за умови деформування повного шару земної кори. Встановлено, що форми і швидкості росту відповідних великомасштабних складок суттєво залежать від розмірів площини зминання земної кори у напрямку дії субгоризонтальної геотектонічної сили і мало залежать від розмірів у напрямку, поперечному до дії сили. При цьому дії субгоризонтальних геотектонічних зусиль під різними кутами до площини зминання земної кори зумовлюють утворення локальних підняттів і опускань земної поверхні. Встановлено також, що змінювання товщини земної кори не приводить до якісних змін загальної картини формування великомасштабних геоструктур у зоні колізії континентів, але проявляються помітні кількісні відміни у швидкості росту відповідних складок. На основе трёхмерной вариационной конечно-элементной методики, в приближении вязкоупругих ортотропных многослойных оболочек, проведено моделирование процесса образования геоструктур в зоне коллизии континентов в случае деформирования полного слоя земной коры. Показано, что эти процессы существенно зависят от размеров плоскости смятия земной коры в направлении действия субгоризонтальной геотектонической силы и мало зависят от размеров в поперечном направлении действия силы. Для плоскостей смятия земной коры с большими размерами в направлении действия геотектонических сил (от 1000 км и больше до 270 км) проявляется процесс образования крупномасштабных поднятий (антиклинориев). Для плоскостей смятия земной коры с соответствующими размерами меньше этой величины характерен процесс образования крупномасштабных опусканий (синклинориев). При этом скорости роста соответствующих крупномасштабных складок зависят от размеров плоскостей смятия земной коры в направлении действия геотектонических сил. Установлено, что под действием субгоризонтальных геотектонических усилий, направленных под разными углами к плоскости смятия земной коры, формируется последовательность локальных поднятий и опусканий земной поверхности, при этом геометрия и скорости роста данных образований также зависят от размеров плоскости смятия земной коры. Изменение толщины земной коры не влияет на качественное изменение общей картины формирования крупномасштабных геоструктур в зоне коллизии континентов. Вместе с тем проявляются заметные количественные различия в скорости роста соответствующих складок. Так, для тонкой земной коры характерны более интенсивные процессы формирования соответствующих геоструктур, по мере увеличения толщины коры (ее общей жёсткости) эти процессы замедляются. Purpose. Comprehension of the continental lithosphere deforming processes in the continental collision zone is the key point in realizing important problems of modern geotectonics, such as geomorphology, orogeny, geostructures compress forming processes and many others. Not accidentally a lot of works are devoted to the study of the questions. There are many aspects of the above-mentioned problems presented in the works. But there still are questions connected with the common mechanical laws of the forming and developing of geostructures in the continental collision zone in certain conditions and scales. The purpose of this article is to understand the geostructures forming processes in the scale of the whole crust layer in order to get the whole picture of geotectonic events.
Design/methodology/approach. Based on the variation finite element method elaborated for viscoelastic foliated orthotropic shells in view of shift rigidity what permits to allow for heterogeneities of both rheological and geometrical characters of the geodynamic objects, in question, we carried out, modeling of the geostructures forming processes in the continental collision zone in the case of the whole crust layer deforming.
Findings. The results of computer modeling of large-scale geostructures forming processes in the continental collision zone show that such processes essentially depend on sizes of the crust contortion planes in the direction of the sub horizontal geotectonic forces action and depend little on the transversal plane sizes. For crust contortion planes with large sizes (in the direction of geotectonic forces action) from 1000 km and more to approximately 270 km, processes of forming large-scale risings (anticlinorium) occur. For crust contortion planes with respective sizes smaller than that value, large-scale fallings (synclinorium) forming processes take place. Growth velocities of respective large-scale folds also depend on sizes of crust contortion planes in the direction of the geotectonic forces action. Subhorizontal geotectonic force actions at different angles to the crust contortion planes causes formation of alternations of local elevations and depressions, with geometry and growth velocities of the local formations also depending on the crust contortion plane sizes. Changing of the crust power was not found to cause qualitative changes of large-scale geostructures forming processes in the collision zone. But there appear to be noticeable quantitative distinctions in the growth velocities of respective folds. For the thin crust, respective geostructures forming processes are more intensive; as the crust thickness becomes bigger, the processes become slower.
Practical value/implications. The obtained results can be used in the study of morphology and orogeny processes, as well as for large-scale geostructures forming processes under large tectonic compression conditions. For further investigation, it is interesting to use the presented method for modeling, in the continental collision zone, geostructures forming processes in different (in scales and compositions) crust vertical incisions.